Color-dye injection of monochorionic placentas and correlation with pregnancy complications. Issue 10 (October 2015) - Lanna, Mariano Matteo; Consonni, Dario; Faiola, Stefano; Schena, Vito; Ratti, Martina; Ferrazzi, Enrico; Rustico, Maria Angela
Abstract Introduction Vascular anastomoses in monochorionic (MC) twin placenta can be easily identified with color-dye injection. The aim of this study is to analyze the relationship between different type of anastomoses and twin pregnancy complications. Methods From January 2011 to October 2014, MC placentas were analyzed with color-dye injection and five group of pregnancies were identified: those that were not complicated (NC), those complicated with selective intrauterine growth restriction (sIUGR), twin–twin transfusion syndrome (TTTS), or twin anemia-polycitemia sequence (TAPS) and those with amniotic fluid discordance (AFD) between twins. Cases of TTTS treated with endoscopic laser coagulation of placenta anastomoses or cases with in utero death of one twin were excluded. Results A total of 118 MC placentas were observed, 58 (49%) NC, 35 (30%) sIUGR, 10 (8%) TTTS, 13 (11%) AFD and 2 (2%) TAPS. The median number of anastomoses was 7 (range 1–15), 8 (2–18), 4 (2–11), 7 (2–13) and 1 (1–1), respectively. At least one artero-venous anastomoses was found in the placenta observed, while the prevalence of artero-arterial anastomoses was 95% for NC, 91% for sIUGR, 60% for TTTS, and 77% for AFD; no TAPS placenta had this type of anastomoses. The diameter of arteroarterial anastomoses was greater in the AFD group (3.3 mm), compared to the NC, sIUGR and TTTS groups (2.3, 2.5 and 1.4 respectively, p 0.04). Discussion In this large serie of MC placenta analyzed with color-dye injection, a specific distribution of anastomoses emerged for twins with amniotic fluid discordance, which points to a need for intensive surveillance.